2013
DOI: 10.1590/s1519-69842013000300016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of some parameters in upscale culture of Haematococcus pluvialis Flotow

Abstract: Growth rate and medium parameters between two bench scale volumes (13-L and 250-L) were compared. Experiments were maintained batch mode and culture parameters were periodically measured during a 13-day period. Culture growth during the cultivation of algae Haematococcus pluvialis was determined qualitatively by cell counting, optical density, dry weight, ash content, amount of chlorophyll-a, total organic carbon content and by direct measuring of medium nutrients and some abiotic aspects. Vegetative cell grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…The doubling time of microalgae biomass was reached on the fifth and sixth day of the cultivation, which is comparable to the results of research [20], in which in the 12 L photobioreactor, the doubling of the number of Haematococcus pluvialis microalgae cells was reached on day 6.9.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The doubling time of microalgae biomass was reached on the fifth and sixth day of the cultivation, which is comparable to the results of research [20], in which in the 12 L photobioreactor, the doubling of the number of Haematococcus pluvialis microalgae cells was reached on day 6.9.…”
Section: Discussionsupporting
confidence: 88%
“…However, the system used for monitoring temperature allowed for controlling it, which is very important for maintaining the highest possible productivity [19]. The results of measurements collected over the course of experiments confirmed that the work of the station in an air-conditioned room at a constant temperature of 22 • C prevents the upper-temperature threshold from being exceeded, as proposed by other authors, e.g., in [20,21]. The systematic increase of temperature over the course of the experiments (Figures 6 and 9) was caused by the heat released by the LED lighting installed inside each storage unit.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Sipaúba-Tavares et al (2015), in the 2-L experiments in NPK and M+NPK alternative media with high nitrogen and phosphorus contents, associated higher cell concentration in NPK medium (light intensity 20 and 60 µmol.m 2 .s -1 ) to phosphate (orthophosphate and total phosphorus) in the medium. Improved algae growth in upscaled cultures (13-L) from the 9 th day assumably was due to total phosphorus and orthophosphate increase (Sipaúba-Tavares et al, 2013).…”
Section: Discussionmentioning
confidence: 98%